Opinions of Library Directors and Librarians on the Handover of Public Library Services to the Local Governments in Turkey - Özden Demircioğlu Faydalı; Bülent Yılmaz (Türk Kütüphaneciliği)
Local governments which have overtaken important functions for providing pub- lic services to the public, and which fulfill these functions according to the needs of the public, are hence the nearest and most effective administrative units to the public. Public Libraries are the social institutions, which have local characteris- tics and provide all the information needs of the public that they serve, for providing assistance for the development of their regions. Local governments and public libraries are closely related to the societies they serve and shape their services according to the needs of the society.